A Novel Mechanism Regulating Dopamine Receptor Type 2 Signal Transduction in Pituitary Tumoral Cells: The Role of cAMP/PKA-Induced Filamin A Phosphorylation - Mangili, Federica; Treppiedi, Donatella; Catalano, Rosa; Marra, Giusy; Di Muro, Genesio; Spada, Anna; Arosio, Maura; Peverelli, Erika; Mantovani, Giovanna (Frontiers in Endocrinology, 2021)
The actin binding protein filamin A (FLNA) is required for somatostatin receptor 2 (SSTR2) and dopamine receptor 2 (DRD2) expression and signaling in GH- and PRL-secreting PitNETs, respectively, playing a role in tumor responsiveness to somatostatin receptors ligands and dopaminergic drugs. FLNA functions are regulated by several mechanisms, including phosphorylation. It has been shown that in GH-secreting PitNETs FLNA phosphorylation on Ser2152 (P-FLNA) switches FLNA function from a scaffold that allows SSTR2 signal transduction, to a signal termination protein that hampers SSTR2 antitumoral effects. Aims of the present study were to evaluate in PRL- and ACTH-secreting PitNETs cell lines MMQ and AtT-20 the effects of cAMP pathway activation and DRD2 agonist on P-FLNA and the impact of P-FLNA on DRD2 signal transduction. We found that forskolin increased (+2.2±0.8-fold, p<0.01 in MMQ; +1.9±0.58-fold, p<0.05 in AtT-20), and DRD2 agonist BIM53097 reduced (-49.4±25%, p<0.001 in MMQ; -45.8±28%, p<0.05 in AtT-20), P-FLNA on Ser2152. The overexpression of a phosphomimetic (S2152D) FLNA mutant in both cell lines prevented DRD2 antiproliferative effects, that were comparable in cells transfected with empty vector, wild-type FLNA as well as phosphodeficient FLNA mutant (S2152A) (-20.6±5% cell proliferation, p<0.001 in MMQ; -36.6±12%, p<0.01 in AtT-20). Accordingly, S2152D FLNA expression abolished the expected ability of BIM53097 to increase or decrease, in MMQ and in AtT20 respectively, ERK phosphorylation, an effect that was maintained in S2152A FLNA expressing cells (+1.8±0.65-fold, p<0.05 in MMQ; -55±13%, p<0.01 in AtT-20). In addition, the inhibitory effects of DRD2 on hormone secretion (-34.3±6% PRL, p<0.05 in MMQ; -42.8±22% ACTH, p<0.05 in AtT-20, in cells expressing S2152A FLNA) were completely lost in S2152D FLNA transfected cells. In conclusion, our data demonstrated that cAMP pathway and DRD2 agonist regulated FLNA activity by increasing or decreasing, respectively, its phosphorylation. Moreover, we found that P-FLNA prevented DRD2 signaling in PRL- and ACTH-secreting tumoral pituitary cell lines, suggesting that this FLNA modification might represent a new regulatory mechanism shared by different GPCRs. In PitNETs expressing DRD2, modulation of P-FLNA might suggest new pharmacological strategies to overcome drug resistance, and P-FLNA might represent a new biomarker for tumor responsiveness to dopaminergic agents.